The Legal Protection of Debtors as Victims of Personal Data Misuse in the Use of Shopee PayLater Service - Leksi, Leksi; Sahay, Tahasak; Wulandari, Vicka Prama (Journal of Law, Politic and Humanities, 2025)
Shopee PayLater services offer convenience in transactions but also pose risks of personal data misuse, thereby underscoring the importance of legal protection under the Electronic Information and Transactions Law (ITE Law) and the Personal Data Protection Law (PDP Law) to maintain consumer trust. Shopee PayLater facilitates transactions through a "buy now, pay later" system; however, it also exposes debtors to potential misuse of personal data. This study examines the legal protection afforded to Shopee PayLater debtors against the misuse of personal data in Indonesia, focusing on the effectiveness of regulatory frameworks and the legal responsibility of Shopee PayLater as a data controller. A normative juridical approach is employed to analyze the Electronic Information and Transactions Law, the Consumer Protection Law, and the Personal Data Protection Law. The findings reveal that, although a solid legal foundation exists, the implementation of data protection remains suboptimal due to weaknesses in cybersecurity systems and unethical debt collection practices. These gaps hinder effective protection for debtors. The researcher recommends enhanced investment in data security, improvement of privacy policy transparency, and stricter government oversight to ensure regulatory compliance and stronger consumer protection